Serum interleukin 1 and interleukin 10 levels in Iraqi leukemic patients with hepatitis G virus infection. - Alani, Muhammad M. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Objectives : This prospective study aimed to estimate interleukins 1 and 10 levels in acute hepatitis (G) in Iraqi patients with leukemiaHepatitis G virus and GB virus C (GBV-C) RNA viruses that were independently identified in 1995, and were subsequently found to be two isolates of the same virus. Blood transfusion is the main risk factor for HGV transmission Immune-mediated mechanisms are believed to play an important pathogenic role in hepatitis G virus infection. Interleukin-1 (IL-1) plays an important role in the inflammatory process. implying that IL-1 may play a role in viral clearance and suggesting that IL-1 has direct antiviral activity, so that IL-1 induces novel antiviral pathways within a cell. Interleukin 10 ( IL-10 )is secreted by T helper-2 type cells (Th2) which may down regulate cell-mediated immune effecter mechanisms important in the host defense against intracellular pathogens. Methods: This cross sectional study was carried out at the national center of hematology , almustansiriya University and department of microbiology in Baghdad medical college in Baghdad, Iraq from January till August 2012. The study involved 33 patients (19 males & 14 females) diagnosed with hepatitis G infection as having a positive IgM antibodies by ELISA technique .Serum IL-1 and IL-10 levels were measured in 33 patients with hepatitis G virus infection and 40 leukemia patients without HGV infections as a control group by ELISA technique . Results: Twenty three patients (70%) with hepatitis G infection had elevated serum IL-1 alpha levels (the normal detection level is below 5 pg/ml), the patient serum IL 1 alpha range 2-37 pg/ml, with a mean 27.813 and SD 32.765 ). There was also a high significant correlation between serum IL-1 alpha level and hepatitis G infection (p value= ± 0.004) when compared with the control group by the t –test Also serum IL-10 level was below the normal detection limit (5-20 pg/ml) in 20 (60%) patients .The 33 patients had serum IL-10 levels (range 0.6 - 9 pg/ml, with a mean 2.213 & SD± 4.745 ) . There was a significant correlation between serum IL-10 level & hepatitis G infection when compared with the control group (p<0.0386 by t- test),so the viral infection may suppress the T helper 2 cells by the gamma interferon . This elevation in IL1 alpha which is an inflammatory cytokine produced by antigen presenting cells , may suggest that IL-1 is an important interleukin to eradicate hepatitis G virus infection. Conclusions: This study showed that serum Th2 cytokines are suppressed (IL10 ) while serum inflammatory cytokine (IL 1 alpha ) is elevated in a proportion of patients with hepatitis G virus infection. However, the elevated IL 1 alpha cytokine levels may represent a systemic response and not as a result of increased local production within the liver.